2015
DOI: 10.12691/ajssm-3-2-1
|View full text |Cite
|
Sign up to set email alerts
|

VO<SUB>2</SUB>max Changes in English Futsal Players after a 6-Week Period of Specific Small-Sided Games Training

Abstract: Futsal is a high-intensity, intermittent sport where accelerations and short sprints are performed at maximal or sub-maximal intensity. These efforts are interspersed by brief recovery periods, during 2 halves of 20 minutes stopping clock. Aerobic endurance inevitably plays a key role in the players' performance. The aim of this study was to analyse the VO2 max progression and the agility (with and without ball) of English futsal players during a 6-week period of small-sided games practice. Two teams volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Indeed, the aerobic fitness level of our participants was lower than those observed in elite futsal players. Despite the similar values of V̇ O 2PEAK in semi-professional players (i. e. those participating in regional or state tournaments; ~ 46 mL·Kg -1 ·min -1 ) 24 , our participants demonstrated significantly lower values compared to elite players (~ 56 mL·Kg -1 ·min -1 ) 25 26 . Considering the predominance of aerobic demands during the 3-minute all-out test, particularly after the initial 30 seconds, it is reasonable to argue that higher aerobic fitness levels contribute to speed maintenance throughout the effort.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Indeed, the aerobic fitness level of our participants was lower than those observed in elite futsal players. Despite the similar values of V̇ O 2PEAK in semi-professional players (i. e. those participating in regional or state tournaments; ~ 46 mL·Kg -1 ·min -1 ) 24 , our participants demonstrated significantly lower values compared to elite players (~ 56 mL·Kg -1 ·min -1 ) 25 26 . Considering the predominance of aerobic demands during the 3-minute all-out test, particularly after the initial 30 seconds, it is reasonable to argue that higher aerobic fitness levels contribute to speed maintenance throughout the effort.…”
Section: Discussioncontrasting
confidence: 57%
“…participants demonstrated significantly lower value in comparison to elite players (~ 56 mL•Kg -1 •min -1 ) [25,26]. Considering the predominance of aerobic demands during the 3-minute all-out test, particularly after the initial 30 seconds, it is reasonable to argue that higher aerobic fitness levels contribute to speed maintenance throughout the effort.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…kg -1. min -1 (Castagna et al, 2009) while other studies heightened the significance of VO 2 max concluding that physical performance discriminates players of different competitive level (Krustrup et al, 2003;Krustrup, Mohr, Ellingsgaard, and Bangsbo, 2005;Pedro et al, 2013). However, Berdejo-del-Fresno andcolleagues (2015) suggested that futsal coaches may increase aerobic capacity of their players throughout an adequate periodization of small sided games by modifying the field dimension and the number of players involved into each task and exercise (Berdejo-del-Fresno, Moore, and Laupheimer, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that this exercise can equally improve the ability [29]. Researchers found in some research reviews that various exercises to increase VO2max can be performed by using a treadmill and running at speed [30], a 15-minute running exercise [31], the fartlek method [32][33][34][35], circuit training [20,36], and smallsided games exercises to increase VO2Max [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%